Vitamin D receptor and vitamin D binding protein gene polymorphisms in patients with asthma: a pilot study - Daina Bastyte; Laura Tamasauskiene; Ieva Golubickaite; Rasa Ugenskiene; Brigita Sitkauskiene (BMC Pulmonary Medicine, 2023)
Abstract Background The effects of vitamin D are exerted by interaction with the vitamin D receptor (VDR) and vitamin D binding protein (VDBP). Polymorphisms in VDR or VDBP genes may affect vitamin D levels, influencing the pathogenesis of asthma and atopy. The aim of this study was to investigate the possible association of VDR and VDBP gene single-nucleotide polymorphisms (SNP), 25-hydroxyvitamin D (25(OH)D), blood eosinophils and total IgE level in subjects with asthma in comparison with healthy individuals. Methods This case-control study enrolled 63 subjects with asthma (45 allergic and 18 non-allergic) and 32 healthy subjects were involved in the study. Sensitization of subjects to inhaled allergens was determined by a skin prick test, lung function was evaluated by spirometry. Blood eosinophil count was determined by standard methods. Serum 25(OH)D and total IgE levels were evaluated by ELISA. Polymorphisms in the VDR and VDBP genes on the 12q13.11 and 4q13.3 chromosomal region were analyzed using TaqMan SNP Genotyping Assay probes. Results In asthma patients with vitamin D deficiency (< 20 ng/ml) the allele G of rs11168293 of VDR was more common than in those having insufficiency (20–30 ng/ml) of vitamin D (63% and 31%, p < 0.05). Moreover, asthmatic subject with rs11168293 G allele has significant higher blood eosinophil count compared to asthmatic without the rs11168293 G allele (8.5 ± 12.3% vs. 5.1 ± 1.5%, p < 0.05). Significantly higher IgE level was found in subjects with allergic asthma with the allele A of rs7041 on VDBP gene than in those without this allele (540 ± 110 and 240 ± 80 IU/ml, p < 0.05). Conclusions The association of polymorphisms in VDBP and VDR gene, the rs11168293 G allele and the rs7041 A allele, with 25(OH)D, blood eosinophil and total IgE level in asthma, let us suggest that vitamin D, VDR and VDBP gene polymorphisms are important in pathogenesis of asthma despite its form in relation to atopy.